How Trust in Social Dilemmas Evolves with Age - Martin G. Kocher (Center for Economic Studies and ifo Institute (CESifo), 2015)
While trust and trustworthiness provide a fundamental foundation for human relationships, little is known about how trusting and trustworthy behavior in social dilemmas is related to age and aging. A few papers use data from surveys such as the World Values Survey to address a potential connection between trust and age. In this chapter, we will mainly focus on trusting and trustworthy behavior elicited with the use of the seminal trust game (Berg et al., 1995) and with games implementing a similar incentivized interaction structure. The results suggest that trust and trustworthiness increase with young age until adolescence. Trustworthiness reaches the level of adults at an earlier age (at around 15-16 years of age) than trusting behavior (around adulthood). Survey results differ from incentivized experiments when it comes to a potential development of trust in adulthood. The former indicate a steady rise in trust levels at a small rate when becoming older, whereas the latter show a decline, starting at an age of about 60 years.
Keywords: C72; C91; 330; trust; trustworthiness; age